2019
DOI: 10.1002/2211-5463.12749
|View full text |Cite
|
Sign up to set email alerts
|

Disorder‐to‐order transition in PE–PPE proteins of Mycobacterium tuberculosis augments the pro‐pathogen immune response

Abstract: A growing body of evidence supports the hypothesis that intrinsically disordered proteins often mediate host–pathogen interactions and modulate host functions for pathogen survival and virulence. Mycobacterium tuberculosis (M.tb) has evolved largely through reductive evolution, with a few exceptions such as the glycine–alanine‐rich PE–PPE/PGRS protein family, which has been expanding in pathogenic mycobacteria. Here, our analyses of the M.tb proteome and secretome revealed that the PE–PGRS subfamily is enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…pe6 cloned into pET-28a was used to express the recombinant protein in ClearColi ® BL21(DE3), an endotoxin-free strain (Lucigen, Middleton, WI, USA). The protein was purified as described earlier with minor modifications ( 28 ). Briefly, recombinant PE6 protein was expressed and purified from BL21 DE3 clear E. coli cells, induced with 0.5 mM Isopropyl ß-D-1-thiogalactopyranoside at 37°C for 4 h till OD 600 nm was reached between 0.4 and 0.6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pe6 cloned into pET-28a was used to express the recombinant protein in ClearColi ® BL21(DE3), an endotoxin-free strain (Lucigen, Middleton, WI, USA). The protein was purified as described earlier with minor modifications ( 28 ). Briefly, recombinant PE6 protein was expressed and purified from BL21 DE3 clear E. coli cells, induced with 0.5 mM Isopropyl ß-D-1-thiogalactopyranoside at 37°C for 4 h till OD 600 nm was reached between 0.4 and 0.6.…”
Section: Methodsmentioning
confidence: 99%
“…We have earlier reported that co-operonic PE32–PPE65 hamper the production of Th1 response ( 27 ). Biophysical investigations revealed that this co-operonic interaction involves disorder-to-order transition that impacts inflammatory cytokines production ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the intrinsically disordered regions of Rv1509 may play a pivotal role in performing important roles in protein function. It has been previously shown that intrinsically disordered regions in proteins may undergo a conformational change to facilitate different functions of a protein, including immune modulation ( 51 ). Besides, the cysteine residues present in Rv1509 can also contribute to modulating protein functions by changing their redox state, which involves changes in intracellular/intercellular disulphide bond ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…These disordered regions provide structural plasticity and conformational adaptability to proteins to enhance their binding promiscuity with various ligands. This could help pathogens to compensate for the genome reduction due to reductive evolution ( 59 ) by resorting to disordered proteins, moonlighting functions and protein promiscuity ( 45 , 60 , 61 ). In-silico analysis for epitope prediction and antigenicity revealed that this protein is highly antigenic.…”
Section: Discussionmentioning
confidence: 99%